GERAKAN IBU SUKSES ASI EKSKLUSIF MELALUI PELATIHAN PIJAT OKSITOSIN DAN AROMATERAPI LAVENDER DI POSYANDU - Yanti Rosmiyanti; Sumitro Sumitro; Desty Lismayanti; Sarini Sarini; Okti Rahayu Asih; Cindy Desrianti; Debi Novita (Bajang Institute, 2025)
Exclusive breastfeeding remains one of the most effective strategies for improving infant health and reducing neonatal morbidity and mortality. However, many postpartum mothers, particularly those who undergo cesarean section, experience delayed lactogenesis and inadequate breast milk production caused by postoperative pain, psychological stress, fatigue, and insufficient breastfeeding support. These conditions often result in the early introduction of formula feeding and decrease the success rate of exclusive breastfeeding. Community-based interventions involving health cadres and mothers are therefore essential to strengthen breastfeeding support at the primary healthcare level. This community service program aimed to improve the knowledge and practical skills of breastfeeding mothers and Posyandu cadres through oxytocin massage training combined with lavender aromatherapy to enhance breast milk production and promote exclusive breastfeeding. The program employed a Participatory Learning and Action (PLA) approach involving education sessions, demonstrations, hands-on practice, mentoring, and program evaluation. Participants consisted of breastfeeding mothers and community health volunteers who attended Posyandu activities. Program evaluation was conducted using pretest–posttest questionnaires and observation checklists to assess participants' knowledge and practical competence. The results demonstrated significant improvements in participants' understanding of lactation management, oxytocin massage techniques, and the appropriate use of lavender aromatherapy. Most participants were able to correctly perform oxytocin massage independently and expressed greater confidence in supporting successful breastfeeding practices. Furthermore, community health volunteers became more competent in providing breastfeeding education and practical assistance to postpartum mothers. This community empowerment program indicates that integrating oxytocin massage training with lavender aromatherapy at the Posyandu level is a feasible, low-cost, and sustainable strategy to strengthen breastfeeding promotion, improve maternal self-efficacy, and support the national exclusive breastfeeding program.